The Future of Health care: Machine Learning - A.Jabbar, M.; Samreen, Shirina; Aluvalu, Rajanikanth (International Journal of Engineering and Technology, 2018)
Machine learning (ML) is a rising field. Machine learning is to find patterns automatically and reason about data.ML enables personalized care called precision medicine. Machine learning methods have made advances in healthcare domain. This paper discuss about application of machine learning in health care. Machine learning will change health care within a few years. In future ML and AI will transform health care, but quality ML and AI decision support systems (DSS) Should Require to address the problems faced by patients and physicians in effective diagnosis.Â